2021
DOI: 10.1159/000513885
|View full text |Cite
|
Sign up to set email alerts
|

Does Dietary Intake Impact Omentin Gene Expression and Plasma Concentration? A Systematic Review

Abstract: Background: Omentin is an adipokine with anti-inflammatory and insulin-sensitizing effects that can play a protective role against cardiovascular disease and diabetes. The aim was to systematically review and summarize the existing evidence on the association between overall dietary intake and omentin gene expression and circulation. Summary: A literature search was conducted in PubMed, Scopus, and Web of Science up to September 2019. Of the 1,940 retrieved articles, 20 relevant studies were included, 6 of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The association between overall dietary intake and omentin gene expression and circulation was investigated. 12 Twenty relevant studies were included; six were observational and eleven were human clinical trials. In the observational studies, omentin serum concentration was reduced by RF and saturated fatty acid intake.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…The association between overall dietary intake and omentin gene expression and circulation was investigated. 12 Twenty relevant studies were included; six were observational and eleven were human clinical trials. In the observational studies, omentin serum concentration was reduced by RF and saturated fatty acid intake.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…Human studies have demonstrated that plasma omentin concentrations are reduced in obese individuals, likely due to inflammation and apoptosis of adipose tissue [ 15 , 49 , 50 ]. Reduction of plasma omentin levels has been significantly correlated with increased waist circumference, bodyweight, dyslipidemia, high blood pressure, and glucose intolerance [ 16 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of animal and clinical studies was recently conducted to assess the association between overall dietary intake and omentin expression and circulation. The results indicated that a long-term diet with reduced fat content and a balanced distribution of fatty acids, i.e., a higher monounsaturated fatty acids and lower saturated fatty acid intake, may increase insulin sensitivity, reduce inflammation, and, consequently, effectively increase the plasma concentration of omentin, but more research is needed to consolidate these assumptions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been observed that high omentin concentration is associated with an increased risk of cardiovascular events in diabetic patients. Omentin is positively correlated with adiponectin while being inversely proportional to leptin [8].…”
Section: Introductionmentioning
confidence: 93%